PENGARUH KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN BERDASARKAN KARAKTERISTIK INDIVIDUAL - Sutanto, Eddy M; Ratna, Athalia (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract: This study aims to examine the effect of organizational commitment on employee performance based on individual characteristics, which include gender, age, marital status, and work experience. Population of the research is all employees of production division. All empoyees are used as the respondents. Results show that organizational commitment influences employee performance. Individual characteristic causes the differences in employee performance is marital status, while gender, age, and work experience do not cause differences in organizational commitment. Keywords: Organizational Commitment, Performance, Individual Characteristics.